ANALISIS KINERJA KANTOR BANDAR UDARA MUTIARA SIS AL JUFRI PALU - Triwahyuni, Febriyanti (Katalogis, 2017)
This research that involved 7 people was conducted in Mutiara Sis Al Jufri airport office Palu. Method used is descriptive and qualitative approach. Data were collected through observation, interview, and documentation. The result of this research revealed that the performance of employees has not maximal yet due to one benchmark indicator fulfilled out of five. Productivity measurement related to the efficiency and the effectiveness of service. It can be done through applied planning in form of program/activity. The suitability of task implementation to achieved work result and the suitability between policies to the implementation of task and work in general, are in accordance with the provisions set. Meanwhile, the other four indicators such as service qualitythat has several aspects of assessment that shows the quality of services provided is still not in accordance with the expectations of society,responsivity, in terms of the level of understanding to task and function in accordance with the applicable regulation and the level of sensitivity showed that the result achieved is not maximal yet, responsibilitywhich tasks and work has been programmed and the execution is also in accordance with the airportpolicies revealed not maximal, as well as accountability whichÂ task and function of each division to the implemented activity by Sis Aljufri Airport Office Palu and its responsibility to the policy maker is still low because not all jobs can be accounted.